Controlled hydrothermal synthesis of different sizes of BaTiO3 nano-particles for microwave absorption. (31st January 2020) - Yan, Yongjie; Xia, Hong; Fu, Yaqin; Xu, Zhenzhen; Ni, Qing-Qing
Abstract: Different sizes of barium titanate (BaTiO3 ) nano-particles were synthesized from precursor H2 Ti3 O7 nanotubes through facile hydrothermal synthesis by using EtOH/H2 O as mixing solvent. Field-emission scanning electron microscopy (FESEM) was mainly used to investigate the effects of solution alkalinity, polarity, and hydrothermal temperature on the size and morphology evolution of BaTiO3 nanoparticles. The results indicate that the presence of strong alkalinity improved the size evenness of BaTiO3 nanoparticles possibly because of the re-dissolution and re-precipitation of TiO3 2− ions. BaTiO3 nanoparticles with the average diameters of approximately 21 and 53 nm were obtained in 9:1 and 1:1 EtOH/H2 O (v/v) hydrothermal medium, respectively. Compared with that, the size of BaTiO3 particles prepared in pure distilled water reached up to ∼512 nm. As for the reason, the addition of EtOH could lower the polarity of hydrothermal medium and make the medium reach the supersaturation more easily, thus limiting the size growth of BaTiO3 particles. In addition, the presence of EtOH led to easier formation of BaTiO3 nanoparticles even at mild hydrothermal temperature, but the particle size was limited even though the temperature was much increased. This is possibly due to lowered interfacial activity in the presence of EtOH. By adjusting solution alkalinity, EtOH/H2 O volume ratios, and hydrothermal temperature, BaTiO3 nanoparticles with the average sizes of approximately 21, 53, 104, 284, and 512 nm, were obtained, and more different and controlled nano-sizes can be expected by further hydrothermal adjustment. In the end, microwave absorption evaluation indicated that decreased size of the BaTiO3 particles enhanced the reflection loss. One possible reason is that the decreased nano-size led to the increased specific surface area of the BaTiO3 nanoparticles.